UJI SENSITIVITAS Escherichia coli YANG DIISOLASI DARI AIR SUMUR GALIAN DEKAT DENGAN Septic Tank TERHADAP CIPROFLOXACIN - Irda Puspita; Ary Andini; Nila Qurrotul A’yun; Anita Anita; Thomas Sumarsono (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
Dug well water is one of the clean water supplies in the village. Contamination often occursdue to one of the bacteria, namely E. coli due to proximity to the septic tank. Several types of bacteriahave been found to have resistance to antibiotics including E.coli. The purpose of this study was todetermine the sensitivity of E.coli isolated from dug well water close to the septic tank againstciprofloxacin. This study used the Kirby-Bauer Diffusion method. The samples in this study were 18dug well water close to the septic tank taken at Village Gelang of RW 01, Tulangan, Sidoarjo. The dataobtained would be analyzed descriptively. Based on the results of the study showed that there were 11samples of positive E.coli wells from 18 wells. E.coli sensitively resulted from 11 samples againstciprofloxacin showed the formation of inhibition zones around the MHA media. The results of thisstudy stated that the well water close to the septic tank is of poor quality because it contains E. coli andis harmful to health if consumed